The socio-pragmatic analysis of Amharic Euphemisms of women - Bamlaku Endegena Zegeye; Endalew Assefa Temesegen; Samuel Handamo Godisso (Cogent Arts & Humanities, 2023)
This study investigated the socio-pragmatic analysis of Amharic euphemisms of women within the frameworks of politeness and relevance theories. The investigation was carried out using a descriptive-qualitative methodology. To accomplish the objective, data were gathered from Amharic native speakers using semi-structured interviews, focus group discussion, and introspection. Hence, using snowball and purposive sampling techniques, informants of elders and youths, males and females, educated and uneducated, urban and rural residences were chosen. The data were analyzed based on the research objectives. Results show that native Amharic speakers believed that it was improper to discuss women’s issues in public, including virginity, pregnancy, menstruation, delivery, abortion, menopause, wife, concubine, and prostitute, at the research areas’ churches, mosques, homes, schools, and hospital realms. Instead, they employed different euphemistic construction mechanisms. In addition, people in the study settings used various euphemistic construction techniques including metaphor, metonymy, idiom, borrowing, circumlocution, overstatement, and understatement. The results also show that research participants in the study locations used a variety of euphemistic formation strategies to avoid taboo utterances, to maintain face, and to demonstrate respect.